Atomic scale crystal field mapping of polar vortices in oxide superlattices - Sandhya Susarla (Nature Portfolio, 2021)
The response of the electronic structure to the non-trivial polarization texture in PbTiO3/SrTiO3 superlattices has not been explored. Here, the authors reveal how the peaks of the spectra shift and change their local electronic structure depending on the position of the Ti cation.